3*(4a-3)=-2a-2a+23

Simple and best practice solution for 3*(4a-3)=-2a-2a+23 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3*(4a-3)=-2a-2a+23 equation:


Simplifying
3(4a + -3) = -2a + -2a + 23

Reorder the terms:
3(-3 + 4a) = -2a + -2a + 23
(-3 * 3 + 4a * 3) = -2a + -2a + 23
(-9 + 12a) = -2a + -2a + 23

Reorder the terms:
-9 + 12a = 23 + -2a + -2a

Combine like terms: -2a + -2a = -4a
-9 + 12a = 23 + -4a

Solving
-9 + 12a = 23 + -4a

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '4a' to each side of the equation.
-9 + 12a + 4a = 23 + -4a + 4a

Combine like terms: 12a + 4a = 16a
-9 + 16a = 23 + -4a + 4a

Combine like terms: -4a + 4a = 0
-9 + 16a = 23 + 0
-9 + 16a = 23

Add '9' to each side of the equation.
-9 + 9 + 16a = 23 + 9

Combine like terms: -9 + 9 = 0
0 + 16a = 23 + 9
16a = 23 + 9

Combine like terms: 23 + 9 = 32
16a = 32

Divide each side by '16'.
a = 2

Simplifying
a = 2

See similar equations:

| 8x-7=105 | | 3x(4a-3)=-2a-2a+23 | | x+2/2=7-x+1/3 | | 2x^3/2*-3^-3/2 | | 2(y-3)=20 | | 125*x^5-171*x^4+103*x^3+224*x^2-508*x+240=0 | | x+x+15+4x-22=1139 | | 2(x-7)=6x+10 | | 65-4x=14x+21 | | 10-3=(2x-1) | | 10-3=5(d-4) | | 10x+30=-5x | | 25^(-3/2) | | 4c+8=-88-8x | | Z=ax^2+3by | | 2*x^4-3*x^3+3*x^2-3*x+2=0 | | 2x+12=-13-9x | | 4x-(2x+6)=3x-26 | | x+(15+x)+(-2+4*x)=1139 | | -3(10x-12)+15x=54 | | 4.2x-6.1y+9.7=0 | | (10-x)(6+x)=64 | | 5x^2-20x-20=16x-4x^2 | | 4(x-3)-6x=-30 | | 6x-10y=70 | | 9*2+-3*4+2*9*2=3*9*2+-3*4 | | 5*(2x+10)=40 | | -12+6x=-66 | | 7x+15=50 | | 78=12 | | 11.5=4.5+((x-4.5)*2) | | 205+20x=315 |

Equations solver categories